DEN-DY (Dental Diary) AS AN EFFORT TO IMPROVE KNOWLEDGE AND BRUSHING SKILLS IN ELEMENTARY SCHOOL CHILDREN - Dandy Dandy; Fahrur Reza. FA; Dyah Saffana Arsinta; Sitti Aminah; Cut Lieddya Rahmita; Salsabila Shafiya Sugiharto; Afifah Ayestina Pelingga; Endah Aryati Eko Ningtyas; Supriyana Supriyana; Bambang Sutomo (Poltekkes Kemenkes Semarang, 2025)
This report discusses community service through the media